DETERMINATION OF NUTRITIONAL AND BIOACTIVE PROPERTIES IN SOME SELECTED WILD GROWING AND CULTIVATED MUSHROOMS FROM TURKEY - Nezahat Turfan; Aysun Pekşen; Beyhan Kibar; Sabri Ünal (Acta Scientiarum Polonorum: Hortorum Cultus, 2018)
This study aimed determining the contents of soluble protein, free amino acid, phenolic, flavonoid, soluble carbohydrate, sugars (glucose, fructose and sucrose) and elements in selected wild growing and cultivated mushroom species collected from various locations of Turkey. Significant differences (P < 0.05) were found for the contents of total free amino acid, soluble protein, phenolic, flavonoid, soluble carbohydrate and sugars. The total free amino acid, soluble protein, phenolic, flavonoid and soluble carbohydrate contents of mushrooms ranged from 33.57–126.57 mg g–1, 2.77–7.55 mg g–1, 28.68–157.39 mg g–1, 8.55–30.66 mg g–1 and 59.89–343.55 mg g–1, respectively. Elemental analysis showed that mushrooms contained significant amounts of potassium (1345.07–9310.17 mg kg–1), phosphorus (1462.44–6159.45 mg kg–1), calcium (18.78–349.15 mg kg–1), sulphur (952.41–12486.63 mg kg–1), iron (80.62–606.26 mg kg–1), manganese (22.65–147.57 mg kg–1), zinc (103.26–522.81 mg kg–1) and selenium (0–115.40 mg kg–1). Nutritient composition varied with mushroom species. The means of total soluble protein, total phenolic, total flavonoid, potassium, phosphorus, sulphur, chlorine, sodium, iron, calcium, manganese, selenium, zinc and copper contents in wild growing mushrooms were found higher than cultivated mushrooms.